Research on the filtering recommendation technology of network information based on big data environment. Issue 4 (18th April 2020) - Cui, Lei
Aiming at the problems of long recommendation time and low accuracy in traditional filtering recommendation methods for network information, a filtering recommendation method based on trusted user rating of network information is proposed. This paper analyses the relationship between the evaluation time of network users and the change of users' interest in the item in different time periods, builds the time forgetting model and time window model of network information, generates time filtering function, filters the historical score of the item by time filtering function, obtains the similarity of users' score, and constructs the trusted user-item rating matrix of network information, to generate the rating recommendation list of target user for network information prediction, and then complete recommendation. The experimental results show that the proposed method has shorter recommendation completion time and higher accuracy.